2012
DOI: 10.1088/0029-5515/52/8/083017
|View full text |Cite
|
Sign up to set email alerts
|

Imposed-dynamo current drive

Abstract: A mechanism for steady inductive helicity injection (SIHI) current drive has been discovered where the current driving fluctuations are not generated by the plasma but rather are imposed by the injectors. Sheared flow of the electron fluid distorts the imposed fluctuations to drive current. The model accurately predicts the time dependent toroidal current, the injector impedance scaling, and the profile produced in the HIT-SI experiment. These results show that a stable equilibrium can be efficiently sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…A simulated version of this discharge shows similar results [52]. This suggests a large-scale transition between the inner and outer regions of the plasma, perhaps contributing to a shear layer such as that expected with impose-dynamo current drive [36]. This phase shift occurs at R ≈ 0.8 − 0.9 m, close to the closed flux surfaces in the plasma.…”
Section: Sparsity-promoting Dmd: First Injector Harmonicsupporting
confidence: 63%
See 1 more Smart Citation
“…A simulated version of this discharge shows similar results [52]. This suggests a large-scale transition between the inner and outer regions of the plasma, perhaps contributing to a shear layer such as that expected with impose-dynamo current drive [36]. This phase shift occurs at R ≈ 0.8 − 0.9 m, close to the closed flux surfaces in the plasma.…”
Section: Sparsity-promoting Dmd: First Injector Harmonicsupporting
confidence: 63%
“…The higher harmonics of the injector frequency are f inj 2 , f inj 3 , and so on. A description of the equilibrium profile and postulated current drive mechanism during sustainment can be found in previous work [36]. The sustainment period of each experimental discharge, indicated by the vertical black lines, is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…A time-smoothed trace of n e from shot 122385 is included in Figure 2 of Ref. 28. n e ¼ 1:5 Â 10 19 m À3 was chosen for the simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The recently discovered imposed dynamo current drive (IDCD) theory explains how HIT-SI plasmas can be sustained stably by the injector-imposed fluctuations with the possibility of current profile control. 28 The present numerical implementation of SIHI is an extension of the original work by Izzo and Jarboe, who ran the first MHD simulations of HIT-SI with NIMROD. 20 The helicity injectors required for current drive are modeled as oscillating normal magnetic and tangential electric field boundary conditions (BCs).…”
Section: Introductionmentioning
confidence: 99%
“…While this method offers the potential for steady-state current drive, and was initially tested on NSTX [5] it was found that discharges generated using this approach could not be successfully coupled to subsequent inductive drive, because of an influx of low-Z impurities. The method is being further developed on smaller machines, including novel approaches that drive steady-state current using a method that relies on steady-state inductive drive [6]. In the second approach, known as Transient CHI, the current on the openfield lines is rapidly reduced on the time scales it takes for the open-field line plasma discharge to fill the vessel.…”
Section: Introductionmentioning
confidence: 99%